Lost in Time: Temporal Monitoring Elicits Clinical Decrements in Sustained Attention Post-Stroke. - Dockree, Paul; Robertson, Ian; O'Connell, Redmond; Kenny, Rose (My University, 2022)
Objectives: Mental fatigue, 'brain fog', and difficulties maintaining engagement are commonly reported issues in a range of neurological and psychiatric conditions. Traditional sustained attention tasks commonly measure this capacity as the ability to detect target stimuli based on sensory features in the auditory or visual domains. However, with this approach, discrete target stimuli may exogenously capture attention to aid detection, thereby masking deficits in the ability to endogenously sustain attention over time. Methods: To address this, we developed the Continuous Temporal Expectancy Task (CTET) where individuals continuously monitor a stream of patterned stimuli alternating at a fixed temporal interval (690 ms) and detect an infrequently occurring target stimulus defined by a prolonged temporal duration (1020 ms or longer). As such, sensory properties of target and non-target stimuli are perceptually identical and differ only in temporal duration. Using the CTET, we assessed stroke survivors with unilateral right hemisphere damage (N = 14), a cohort in which sustained attention deficits have been extensively reported. Results: Stroke survivors had overall lower target detection accuracy compared with neurologically healthy age-matched older controls (N = 18). Critically, stroke survivors performance was characterised by significantly steeper within-block performance decrements, which occurred within short temporal windows (˜3 ½ min), and were restored by the break periods between blocks. Conclusions: These findings suggest that continuous temporal monitoring taxes sustained attention processes to capture clinical deficits in this capacity over time, and outline a precise measure of the endogenous processes hypothesised to underpin sustained attention deficits following right hemisphere stroke.
PUBLISHED
Keywords: Mental fatigue; Continuous Temporal Expectancy Task (CTET); right hemisphere stroke; Sustained Attention; Stroke; Right Hemisphere; Clinical Assessment; Attention; Ageing